The Role of Second Language Acquisition (SLA) Theories in TESOL Methodology - Aip Syaepul Uyun; Eva Medi Kulsum (Gunung Djati Conference Series, 2023)
This paper aims to give a brief description on depth understanding of Second language acquisition theories and its role in TESOL methodology. It is to answer the issues that still occurs in English instruction in Indonesia. Thousand teacher trainings, and conferences, merely held to discuss on how is the best way to teach English, yet those measures is still remaid many homeworks. Thus it becomes the ideas of writing this paper. It is to know what is the fundamental theories can be used as a principles of TESOL in Indonesian context. The writer has taken an action and deeply studied about many literatures on this topic. The main reference used is Stephen Krashen book in 1982 of second language acquisition. The findings believes that the ideas of teaching second language is devided into two aspects. The first is how to teach a second language, it talks about technical methodology such as methode and technique that teacher use in class, and the second is the understanding on how second language can be acquired, it talks about teacher understanding of theories of second language acquisition. Here in this paper, the reseracher more focuse on the second ideas on the role of second language acquisition theories in TESOL Methodology